2014
DOI: 10.1016/j.sleep.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in shift work

Abstract: The present study highlights insomnia as an important component of the sleep difficulties experienced by shift workers. Insomnia may exacerbate certain physical and mental health problems of shift workers, and impair their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 45 publications
4
77
2
7
Order By: Relevance
“…In the study of Shao et al, most of shift work nurses had a problem with sleep (22). In Vallieres et al study, insomnia in shift workers worsened certain physical and mental health problems in them and impaired their quality of life (23). In another study by Asaoka et al conducted on 1202 nurses, the prevalence of insomnia was 24.4%, they had lower healthrelated QOL, more severe depressive symptoms, and more errors than those without insomnia.…”
Section: Discussionmentioning
confidence: 97%
“…In the study of Shao et al, most of shift work nurses had a problem with sleep (22). In Vallieres et al study, insomnia in shift workers worsened certain physical and mental health problems in them and impaired their quality of life (23). In another study by Asaoka et al conducted on 1202 nurses, the prevalence of insomnia was 24.4%, they had lower healthrelated QOL, more severe depressive symptoms, and more errors than those without insomnia.…”
Section: Discussionmentioning
confidence: 97%
“…Keywords circadian depression diabetes neuroticism nightshift obesity shiftwork well being BACKGROUND Shiftwork is associated with detrimental effects on health and wellbeing, including increased risk of diabetes [1][2][3][4][5] and sleep problems, [6][7][8] higher body mass index (BMI) [1,[9][10][11][12], and increased signs of anxiety and depression. [8,13,14] Shiftworkers were once predominantly male, manufacturing sector workers, but this is no longer the case; a recent government survey reported that security services, transport and communications industries were the most common occupation of shiftworkers in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rotational-shift workers, including those who work night shifts (e.g., nurses, police officers, airline pilots, and truck drivers), have been reported to experience greater life-or work-related problems relative to day-shift workers [4][5][6]. The problems related to rotational-shift work affect sleep [4][5][6][7] and work performance [4][5][6]8]; furthermore, they lead to an increase in lifestyle-related health [9] risks such as obesity, diabetes [10], heart disease [11], depression, hypertension [12][13][14], and cancer [15]. Therefore, the improvement of rotationalshift workers' sleep quality and quality of life is important.…”
Section: Introductionmentioning
confidence: 99%